Elvis Sings for the BBC: broadcast branding and digital media design - Grainge, Paul (Sage, 2010)
This essay uses a striking example of digital remix promotion - BBC Radio 2’s Elvis ad - to examine developments in the contemporary branding and broadcast environment. Developing work by John Caldwell, it examines the Elvis ad as a ‘deep text’, a promotionally reflexive articulation by media industries about the nature of corporate media identity and aesthetics. Suggestive of the BBC’s attempt since the late 1990s to make its brand ‘sing’, and relating specifically to the visualization of radio in the digital age, the essay uses the Elvis ad to investigate the performance of network personality in the multi-channel era, the growing role of brand/design companies such as Red Bee Media, and the operational and ontological transition of the BBC to a digital media world. More generally, the essay considers the relation of found-footage promotion to the ‘spatialization of audiovisual culture’.